تسجيلات إضافية من النوع السمكي الغضروفي، القوبع اللاسع Himantura uarnak (فصيلة Dasyatidae) في الساحل السوري - علي مالك; سعد أديب; رينو كريستيان; كابيبي كريستيان (Latakia University Journal -Biological Sciences Series, 2013)
يهدف هذا المقال إلى تأكيد وجود نوع السمك الغضروفي Himantura uarnak (Forskal, 1775) في المياه البحرية السورية، من خلال توثيق إضافي لعينتين تم صيدهما، جنوب مدينة طرطوس ( 35º 55¢ E & 34º 42¢ N )، كانت العينتان بالغتين جنسياً، الأولى أنثى والثانية ذكر، بلغ عرض قرص العينة الأولى 1078 ملم والثانية 840 ملم، وبلغ وزناهما 31,450 كغ و15,580 كغ على التوالي. تم تسجيل القياسات التصنيفية المورفومترية للعينتين لأقرب ملم، ونسبت قياسات كل عينة إلى عرض قرصها، وحفظت قطع من الجلد والذيل من العينة الأولى ضمن المجموعة السمكية في مخبر علوم البحار بجامعة تشرين بكلية الزراعة (سوريا). This paper aimed to present additional records of Honeycomb stingray Himantura uarnak (Forskal, 1775) (Chondrichthyes: Dasyatidae) off the Syrian coast (Eastern Mediterranean). Two specimens were captured in Syrian waters (Tartous coast) 35º 55’ 31”E and 34º 42’ 40’’ N. The first specimen was an adult female, and the second an adult male; they measured 1078 mm and 840 mm disk width, and weighed 31.450 kg and 15.580 kg, respectively. Morphometric measurements were recorded to the nearest millimeter, and reported as percentage of the disk width (%DW). Pieces of skin and tail were deposited in the Ichthyological collection of the Marine Sciences Laboratory, Agriculture Faculty of Tishreen University, Syria.